Prodigal offspring: Organizational sociology and organization studies. (July 2020) - Scott, Alan
Academic disciplines are defined not primarily by their object but by their (theoretical and methodological) approach to that object, and by their claim to a monopoly over it. Even where that monopoly claim has been highly successful, it remains contestable. For example, economics, perhaps in this respect the most successful social science, finds its object – the economy – contested by political economists and economic sociologists. Whereas economics has successfully marginalized potential competitors, sociology has remained a broad church. Attempts to impose theoretical and methodological order on the discipline have met with resistance, and eventually failed. Moreover, sociology has never really reached consensus on what its object is; 'society', 'social facts', 'social action' were the classical options, with the list growing over time (social networks, rational action, actor networks, etc.). Thus, while we can speak of 'heterodox economics' there is insufficient orthodoxy to speak of 'heterodox sociology'. This has an obverse side. Precisely because of the weakness of its monopolistic claims, sociology has been very productive in spawning new disciplinary fields, which, rather than remaining within sociology's weak gravitational pull, successfully establish themselves as separate disciplines or 'studies'. Criminology, industrial relations, urban studies and organization studies are the most obvious examples. In light of this, this article addresses two questions: (1) What happens to these new fields when they break free of the parent discipline, and to the parent discipline when they do? (2) If one effect on the 'offspring' is a loss of disciplinary orientation (as the rationale for this special issue suggests) what, if anything, has contemporary sociology to offer OS as a potential source of reorientation?